2022
DOI: 10.5194/acp-22-6449-2022
|View full text |Cite
|
Sign up to set email alerts
|

Measurement report: Optical properties and sources of water-soluble brown carbon in Tianjin, North China – insights from organic molecular compositions

Abstract: Abstract. Brown carbon (BrC) aerosols exert vital impacts on climate change and atmospheric photochemistry due to their light absorption in the wavelength range from near-ultraviolet (UV) to visible light. However, the optical properties and formation mechanisms of ambient BrC remain poorly understood, limiting the estimation of their radiative forcing. In the present study, fine particles (PM2.5) were collected during 2016–2017 on a day/night basis over urban Tianjin, a megacity in northern China. Light absor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 126 publications
4
22
0
Order By: Relevance
“…In addition, the fluorescent components of WSOC were measured utilizing an excitation-emission matrix (EEM) fluorometer (Aqualog, HORIBA) within the excitation and emission wavelength ranges of 240−550 nm and 246−828 nm, respectively. 52,53 The EEM fluorescence spectra data were analyzed by the parallel factor (PARAFAC) model performed with the software package Solo (Eigenvector Inc.). 52,54 Water-soluble species including SO 4 2− , NO 3 − , and NH 4 + were analyzed using an ion chromatography system (ICS-5000+, Thermo).…”
Section: Study Site and The Sampling Methodmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the fluorescent components of WSOC were measured utilizing an excitation-emission matrix (EEM) fluorometer (Aqualog, HORIBA) within the excitation and emission wavelength ranges of 240−550 nm and 246−828 nm, respectively. 52,53 The EEM fluorescence spectra data were analyzed by the parallel factor (PARAFAC) model performed with the software package Solo (Eigenvector Inc.). 52,54 Water-soluble species including SO 4 2− , NO 3 − , and NH 4 + were analyzed using an ion chromatography system (ICS-5000+, Thermo).…”
Section: Study Site and The Sampling Methodmentioning
confidence: 99%
“…The analytical errors for OC, EC, and WSOC concentrations were within ±10% through a duplicate analysis of each filter. In addition, the fluorescent components of WSOC were measured utilizing an excitation-emission matrix (EEM) fluorometer (Aqualog, HORIBA) within the excitation and emission wavelength ranges of 240–550 nm and 246–828 nm, respectively. , The EEM fluorescence spectra data were analyzed by the parallel factor (PARAFAC) model performed with the software package Solo (Eigenvector Inc.). , Water-soluble species including SO 4 2– , NO 3 – , and NH 4 + were analyzed using an ion chromatography system (ICS-5000+, Thermo). The relative water content (RWC) of particles was calculated as RWC (%) = 100% × ( W I – W D )/ W I , where W I (g) and W D (g) are the initial weight of the collected particles and the dry weight of the particles after being freeze-dried, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In Fig. S6b, our SFEBrC values from burning residential solid fuels over the TPL region were lower than paddy-residue burning over the Indo-Gangetic Plain (Choudhary et al, 2021) and rice straw burning in Anhui Province, China (Zhao et al, 2022), but they were comparable with those from the burning of maize straw in Shaanxi province (Lei et al, 2018b) and from ambient aerosols over heavily polluted northern Chinese cities, including Tianjin, Erenhot, Zhangbei and Jinan Deng et al, 2022). These phenomena confirmed that the heavy BrC loadings from residential fuels can cause high radiative forcing effects over TPL regions.…”
Section: Estimation Of the Potential Radiative Effects Of The Identif...mentioning
confidence: 79%
“…The method based on "SFE" can effectively assess the potential direct radiative forcing of BrC light absorption emitted from solid fuel combustion in this study. However, the radiation effects caused by aerosol scattering were ignored in the estimation and only the absorption was considered (Deng et al, 2022). Therefore, the formula for calculating radiative forcing in the range of 280-700 nm can be simplified as follows (Lei et al, 2018b;Zhang et al, 2020):…”
Section: 4mentioning
confidence: 99%
“…These results indicate that secondary CHO organic aerosols have obvious bias in the formation processes. At low SOA load, especially monoterpene derivatives, secondary CHO organic aerosols are dominated by conjugated polyene compounds with low oxygen content and high saturation, while with the increased of SOA load, multi-step oxidation formed the O-rich compounds containing monophenyl ring, which may be important light-absorbing chromophores in the atmosphere (Deng et al, 2022).…”
Section: Cho Compoundsmentioning
confidence: 99%